STRATEGI PEMBANGUNAN RUMAH TIDAK LAYAK HUNI DALAM MEMINIMALISIR PERMUKIMAN KUMUH DI KOTA BOGOR - Septianisyah Dian Hayati; Abu Bakar Iskandar; Ginung Pratidina (Jurnal Governansi, 2018)
This research is based on time problem which has no certainty. in the House Unfulfilled House program in Bogor City there are still problems in terms of development, implementation that is not in accordance with the appropriate program. The purpose of this research is (1) To know the implementation and Program In Program House Not Eligible Hunidi Bogor City, (2) To know the inhibiting factors in the implementation of Program Housing Incomplete Bogor City, (3) Formulate the strategy of construction of Unfit House in Bogor city. This research uses qualitative method that is research that produce descriptive data in the form of oral or oral words from people and behavior that can be examined. The results of this study indicate that 1) Implementation and procedures in the program RUTILAHU In the city of Bogor, has not run well as in the development stage and community programs that are not evenly distributed and many homes that have not been realized in home improvement. 2) Unfit Housing Program in Bogor City that has not been equitable in terms of development, information and socialization and unfavorable process. 3) The formulation of the results of this study responsiveness in the needs of the people of Bogor City Government research results are sufficient to provide programs that can help the poor, one of which is RUTILAHU program. Keywords: Development Strategy, Inhabitable House, Slum Area.